Audit specialisation in Malaysia - Md Ali, Azham (Universiti Utara Malaysia, 2006)
Recent events, especially with respect to the failure of Enron, have created an increased awareness regarding the importance of high quality audit.In general, prior research has used the Big 6/non-Big 6 dichotomy to differentiate audit quality (Palmrose, 1986).However, a second body of research suggests that industry specialisation represents an additional level of audit quality beyond the Big 6/non-Big 6 dichotomy.In this study, the focus is on trends in industry specialisation from 1999 to 2002 by applying audit firm industry market share measure as proxy for audit firm industry expertise or specialisation.Specifically, the market share approach assumes that by observing the relative market shares of the audit firm servicing a particular industry, one can deduce those which may be known as industry specialists (Zeff and Fossum, 1967; Rhode et al., 1974; Schiff and Fried, 1976; Dopuch and Simunic, 1980, 1982; Danos and Eichenseher, 1982; Craswell and Taylor, 1991; Craswell et al., 1995; Kwon, 1996; Beelde, 1997; and Hogan and Jeter, 1999).With data coming from annual reports of companies listed at the Kuala Lumpur Stock Exchange (KLSE – now, Bursa Malaysia) and industry specialists defined as market leaders with market share greater than 20 percent of audit services (in terms of the number of clients) within a client specific industry, it is found that Ernst and Young specialising in construction and plantation, KPMG in industrial products, PricewaterhouseCoopers in finance and Arthur Andersen in finance, plantation, technology and trading/services.With regard to audit market share distribution across industries, over time and over a couple of clients’ characteristics (audit fees paid out and revenues earned), it is found that four of the Big 5 audit firms (minus Deloitte Touche) take a lion share.Based on all this, in the Malaysian context in regard to the listed companies segment, the audit market could be categorised as tight oligopoly.